Management of Unruptured Brain Aneurysms: Retrospective Analysis of a Single Centre Experience. Issue 3 (1st June 2013) - Moscato, G.; Cirillo, L.; Dall'Olio, M.; Princiotta, C.; Simonetti, L.; Leonardi, M.
Embolization is very effective in preventing bleeding of unruptured aneurysms with lower rates of mortality and morbidity than surgical treatment. Neurosurgery remains, however, a good alternative. This retrospective analysis examined data stored the digital database of Bellaria Hospital Radiology Department, evaluating patients, treatments and devices used as well as outcomes and complications. Therapy should be tailored to each individual case to offer each patient the best treatment. Out of 265 unruptured intracranial aneurysms detected, 182 were treated by embolization. 16 cases presented complications (12 only radiologically found); severe clinical consequences occurred in 3%: one ischaemia and five haemorrhages. Conservative treatment was adopted in 21 patients. Long-term follow-up is mandatory as aneurysms could increase their size and develop an irregular morphology in ten years' time. Endovascular embolization is a very effective treatment with positive outcomes in the majority of cases and a percentage of retreatments of 8%. In order to increase the number of successful cases, a multidisciplinary cooperation with neurosurgeons is strongly recommended.